Distribution of Cadmium in Sweet Corn Grown on a Peat Soil and Its Implication on Food Safety - Rini Susana; Denah Suswati (UNIVERSITY OF LAMPUNG, 2018)
Cadmium (Cd) is a heavy metal that can contaminate agricultural soils, in which one of the sources of Cd in agricultural soils is the use of phosphate fertilizers. Some plant species are known to have the ability to accumulate large amounts of Cd in their organs despite the Cd content in soil is relatively small. Cadmium distribution in various organs of plants also shows a diverse variation. Maize is able to accumulate Cd in its organs, either in roots, leaves or grains. This study aims to determine the distribution of Cd in sweet corn plants grown on a peat soil. Samples of maize plants were taken from nine maize fields in the village of Rasau Jaya 1, Rasau Jaya subdistrict, Kubu Raya district, West Kalimantan. The cultivars of sweet corn planted were Zea mays saccharata cultivar Bonanza and Zea mays saccharata cultivar Secada. Samples for roots, leaves, stems and panicles were taken at the stage of early grain filling. Grain samples were taken at the phase of fresh pod consumption. The Cd contents in the plant organ tissues were determined using dry ashing method. The results showed that the distribution of Cd in plant organs of sweet corn cultivars Secada and Bonanza follows the pattern of Cd in leaves > roots > grains > panicles > stems. The leaves contain the highest concentration of Cd, while the stems contain the lowest amount of Cd. The Cd concentration in leaves is about 3.5 times higher than that in grains, and 1.5 times higher than that in roots. The average Cd content in grains of sweet corn is 0.037 mg kg-1, which is still below the safe limit of Cd content in grains allowed by the Standar Nasional Indonesia, i.e. 0.2 mg kg-1.